STUDIES ON LYMPHOGRANULOMA VENEREUM : I. DEVELOPMENT OF THE AGENT IN THE YOLK SAC OF THE CHICKEN EMBRYO - Rake, Geoffrey (The Rockefeller University Press, 1942)
Making use of the fact that the cells of the yolk sac of the developing embryo are readily infected with the agent of lymphogranuloma venereum and that the virus bodies can be readily observed in these cells because of the structure of the latter, the development of this agent has been followed at short intervals. It has been found to go through a regular cycle of development similar to that described for psittacosis in the spleen and less fully for lymphogranuloma venereum in the brain of infected mice. The development as observed microscopically can be shown to run parallel to changes in the infective titre of the yolk sac as tested in other eggs.